A PRE TEST AND POST TEST DESIGN TO ASSESS THE EFFICACY OF VIRECHANA AND ARDHAMATRIKA BASTI IN GOUTY ARTHRITIS W S R TO VATARAKTA (AYUSHDHARA, 2019)
The health of an individual depends on his diet and lifestyle. The rapid modernization, fast food culture, stressful and speedy life leads too many serious health issues. Among such health issues Vatarakta is one. A chronic disease or illness is defined as a condition which develops gradually through years because of frequent and continuous exposure to abnormal dietary, lifestyle or environmental factors. In Vatarakta these lifestyle changes causing inflammatory changes to joint leading to pain and swelling. Vatarakta in Ayurveda is considered as one of chronic illness which is commonly seen affecting nearly 14-17% of population every year. Vatarakta is more distressing and common metabolic disorder prevalent in present era. Vatarakta is correlated with gout in modern science. Gout is an abnormality of purine metabolism causes hyperuricemia and deposition of monosodium urate crystals in joints. Pain is predominant symptom of gout; it disturbs day-to-day life of the patient. Shodhana Chikitsa is considered as the best line of treatment. Treatment aims to eliminate the Sanchita mala (Serum uric Acid) and to bring back Vata and Raktha to its normalcy. Among the Shodhana procedures Vasti and Virechana are considered as the main line of treatment for Vatarakta. Here in this study 100 subjects are randomly selected and grouped in 2 groups A and B, in Group A Ardhamatrika Niruha basti and in Group B Nimbamruthadi eranda Virechana is done. Both the therapy shows significant results in patients of Vatarakta. But after statistical test and percentage wise results Basti group shows more improvement in uric acid levels and other symptoms.